17th January 2nd Sunday after Epiphany - Browning, Derek (2015)
The article presents the author's perspectives on a biblical reading for January 17, 2016, the second Sunday after Epiphany of Jesus Christ. In this biblical reading Jesus Christ features the importance of the sacrament of marriage and hospitality during the wedding celebration. This biblical reading also conveys the value of divine generosity among Christians.
Keywords: EPIPHANY season; Jesus Christ; Jesus Christ -- Miracles; Miracles; Religious Aspects; TURNING water into wine at the wedding at Cana (Miracle); WEDDING etiquette; Weddings